REPOST LIVE STREAM YOUTUBE PADA TIKTOK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA: Repost Of Youtube Live Streams On Tiktok Based On Law Number 28 Of 2014 Concerning Copy Right - Rania Maharani; Aline Gratika Nugrahani (Faculty of Law, Universitas Trisakti, 2025)
Repost activities in the current era have become troubling, reposts that aim to disseminate information are very permissible, but not a few reposters abuse this activity, some parties repost without having permission from the creator and those who repost often seek profit from this activity. Like the case experienced by Youtuber Windah Basudara, his live streaming gaming content was reposted by an irresponsible party and commercialized, while live streaming content is a copyrighted work protected by law. The problem discussed in this paper is whether reposting live streaming without permission is allowed. This type of research is normative which is descriptive in nature, using primary and secondary data, collecting data by literature study which is analyzed with qualitative data, and drawing conclusions in a deductive manner. The results and conclusions of this research are repost activities carried out without permission and profit is an act of copyright infringement. This is in accordance with the regulations in Article 40 of the UUHC that cinematographic works are works protected by copyright.